Desain panel peredam suara dari material cangkang telur dan ampas teh - Christmastuti Nur (ARTEKS : Jurnal Teknik Arsitektur, 2023)
Noise reduction in residential and other types of buildings in urban areas is becoming more important. However, the cost of sound-absorbing materials is still prohibitively expensive for some people. The objective of this study is to create alternative sound-dampening materials from composites made from household waste, specifically egg shells and tea waste. The hypothesis of this study is that because eggshell is a porous material and tea waste is a fibrous material, it has the ability to absorb sound. The sound absorption test was performed in accordance with ASTM E-1050-98, a standard for testing impedance and absorption with a digital frequency analysis system. The highest sound absorption coefficient of the egg shell composite was 0.97 at a frequency of 2392 Hz (NC 35), while the highest sound absorption coefficient of the tea waste composite was 0.592 at a frequency of 1960 Hz (NC 30). The results of the analysis show that both types of composites can be used as alternative sound absorbing materials in residential and similar types of buildings.